2020
DOI: 10.3390/insects11060329
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Adult Mosquito Trapping Methods to Assess Potential West Nile Virus Mosquito Vectors in Greece during the Onset of the 2018 Transmission Season

Abstract: West Nile virus (WNV) threatens the health of humans and equines worldwide. Culex (Cx.) pipiens complex mosquitoes are major vectors but numerous other species have been implicated. Due to variations in blood-feeding behaviour, Cx. pipiens biotypes and hybrids influence transmission, from enzootic cycles (between mosquitoes and birds), to spill-over transmission to humans and equines. In this study, mosquitoes were collected in May–June 2018 during the early period of the transmission season from two regional … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 64 publications
2
9
0
Order By: Relevance
“…In this study, mosquito screening for WNV showed that the majority of positive samples for WNV were detected in the East Attica, followed by the South Sector of Attica (Table 4). In the RU of PF, WNV-positive pools in mosquitoes were detected in both years, while in the study of Bisia et al (2020) [18], no positive pool was detected in 2018. The region of MS has a warm temperate climate with hot dry summers and mild winters and displays characteristics to sustain WNV transmission cycles [96].…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…In this study, mosquito screening for WNV showed that the majority of positive samples for WNV were detected in the East Attica, followed by the South Sector of Attica (Table 4). In the RU of PF, WNV-positive pools in mosquitoes were detected in both years, while in the study of Bisia et al (2020) [18], no positive pool was detected in 2018. The region of MS has a warm temperate climate with hot dry summers and mild winters and displays characteristics to sustain WNV transmission cycles [96].…”
Section: Discussionmentioning
confidence: 74%
“…The installation and circulation of WNV in Greece is a fact, while extensive studies have been performed on its circulation since 2010 [10][11][12]14,18,23,30,[33][34][35]. However, predicting periods and circulation areas of the virus are difficult due to complex interactions of multiple involved factors [23,38,100].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations